Incarcerated adult femoral hernia containing a fallopian tube - Oakenful, Cindy (Australas J Ultrasound Med, 2015)
Femoral hernias are not common in the adult population however they are often associated with higher rates of incarceration compared to other hernia subtypes. Subsequently they have an increased need for emergency surgical intervention. It has been well documented in the literature that femoral hernia sacs can contain an array of anatomical structures and rarely this includes fallopian tube. Within the limits of the authors' literature review, this case represents the only documented pre‐operative diagnosis of femoral hernia containing fallopian tube.